Rationing the size of the irreducible reserve of locomotives at the turnover stations - E. A. Sotnikov; M. M. Gonik; S. V. Khomyakov; S. V. Mikhailov (Вестник Научно-исследовательского института железнодорожного транспорта)
Based on the model developed by the specialists of JSC "VNIIZhT" for determining the rational dimensions of the irreducible reserve of locomotives at the turnover stations (Мнр), mass calculations were performed to determine the size of the reserve depending on the influencing factors. The value of Мнр substantially depends not only on the size of the motion, but also on a number of other factors that are taken into account in this model. Using the model, it is possible to carry out calculations to establish the influence of various factors on the value of М . The first question of this study is the analysis of the dependence of the magnitude of Мнр on various factors (multivariate analysis), determination of its significance and ranking of factors. The second question is the determination of the numerical values of М in the form of practical recommendations for its use in determining the size of the minimum reserve of locomotives at the turnover stations, taking into account the various effects of the factors under consideration: average daily train flows and its fluctuations per day, oddness of operating trains, planning quality (deviation of planned train flows from actual), the level of fulfillment of the tasks of the plan for sending locomotives by a single follow-up at the turnover station. In total, 1575 variants of the work of locomotive turnover stations were calculated, in each of which the sizes of the irreducible reserve of locomotives are determined by the results of work for 400 days. The total data set amounted to 630 thousand results. As the result, the significance of the factors is established, its ranking is made. Based on the results of modeling, a table of standard values of the irreducible reserve of locomotives at the turnover stations was developed, which can be used by the employees of the JSC "Russian Railways" for practical purposes. This will improve the quality of execution of the train schedule and reduce unproductive downtime of trains ready for departure at locomotive turnover stations.